2017
DOI: 10.3390/ijms18122664
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Serum APE1/Ref-1 in Experimental Murine Myocarditis

Abstract: Myocarditis is an inflammatory disease of the myocardium that causes cardiogenic shock and death. However, endomyocardial biopsy that is, the gold standard for a diagnosis is limited. Apurinic/apyrimidinic endonuclease 1/redox effector factor-1 (APE1/Ref-1) is a multifunctional protein, which is involved in DNA-based excision repair pathway, and in redox signaling, its changes are observed in various cardiovascular diseases including hypertension and coronary artery disease. We analyzed serum APE1/Ref-1 in exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Previous studies have demonstrated that APE1/Ref-1, a typical nuclear protein, is also present in the extracellular milieu of cells associated with chronic diseases [11,13,28,29,30]. Identification of its secretory pathway would clarify whether the detection of APE1/Ref-1 in extracellular samples is an experimental artifact or is the result of a controlled cellular response to certain stimulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that APE1/Ref-1, a typical nuclear protein, is also present in the extracellular milieu of cells associated with chronic diseases [11,13,28,29,30]. Identification of its secretory pathway would clarify whether the detection of APE1/Ref-1 in extracellular samples is an experimental artifact or is the result of a controlled cellular response to certain stimulators.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular APE1/Ref-1 plays the role in disulfide bond exchange within the TNF receptor, causing inhibition of vascular inflammatory signals [10]. Stimulation of the APE1/Ref-1 secretion is triggered by its acetylation, as shown by diminished secretion level of the mutant APE1/Ref-1(K6/7R) due to mutated lysine, thus supporting the critical role played by lysine acetylation in various cardiovascular diseases [28]. Although deacetylation of Ac-APE1/Ref-1 followed time-dependent kinetics, eventually reaching an optimum, the recovery mechanism of Ac-APE1/Ref-1 to its non-acetylated form with respect to its reductase activity requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…APE1/Ref-1 is also highly expressed in retinal pericytes, choroidal endothelial cells and retinal endothelial cells and is upregulated in tissues where there is inflammation [ 28 , 29 , 30 ]. Furthermore, evidence suggests that secretion of APE1/Ref-1 into the extracellular milieu can act as a serological biomarker for vascular inflammation and other chronic diseases [ 27 , 31 , 32 , 33 ]. Acetylated APE1/Ref-1 has also been shown to be secreted from cells via the ATP binding cassette transporter A1 [ 33 ].…”
Section: Ape1/ref-1mentioning
confidence: 99%
“…Basically, APE1/Ref-1 plays roles in transcriptional regulation through redox modification and base excision repair [3]. Since it was first reported in 2013 that APE1/Ref-1 secretion is increased by intracellular hyperacetylation [4], it has subsequently been reported that its secretion is increased in lipopolysaccharide-induced endotoxemic animal models [5], apolipoprotein E-deficient mice fed Western-type diets [1], and patients with coronary artery disease [6], suggesting its usefulness as a new biomarker for vascular inflammation.…”
Section: Introductionmentioning
confidence: 99%